PRZYRZECZENIE PUBLICZNE - WYBRANE PROBLEMY SEMIOTYCZNE I DOGMATYCZNE - Mularski, Krzysztof (Wydział Prawa i Administracji UAM, 2008)
Some of the achievements of the modem semiotics have been used in the paper to analyse the regulations of a public promise of a reward as laid down in the Polish Civil Code (art. 919 and the following). In the author’s opinion, public promise of a reward - contrary to the practically unanimous opinion of civil law dogmatics - can be addressed to a definite subject, indicated by an individual name. The paper also presents certain specific social functions that can be performed by the institution of public promise. Public promise o f a reward, which should be considered as an inducement to undertake a certain action, allows to realise some positively regarded situations, the achievement of which would not be possible without the existence of a civil law contract. However, a reward cannot always be considered as a “performance” in terms of civil law. Some rewards require that certain conventional actions must be taken, and be based on rules which ensure full voluntariness on the part o f the subject undertaking such an action. Consequently, this kind of rewards cannot be enforced (in the meaning of the term) and the sanction for non-fulfilment of a promise should be sought among the rules which regulate infringement of personal rights rather than non-performance of a contract. 66
PUBLIC PROMISE OF A REWARD: SELECTED DOGMATIC AND SEMIOTIC ISSUES